Pengembangan Tes Bertahap Terpadu untuk Mengidentifikasi Pemahaman Konsep IPA dan Miskonsepsi Peserta Didik SMP Kelas VII - Desak Nyoman Srinadi; Putu Budi Adnyana; Putu Artawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to produce an integrated, valid, and practical step-by-step test that is valid, reliable, and practical to identify students' understanding of science concepts and misconceptions. The study was conducted based on the Plomp & Nieveen model and test development steps by Oriondo & Dallo-Antonio. The subject of this study is an integrated gradual test. The object of this research includes the characteristics, validity, reliability, practicality, and profile of students' understanding of concepts and misconceptions in science learning. Data was collected through interviews, document studies, questionnaires and tests. The data was analyzed qualitatively and quantitatively. The results of the study obtained the characteristics of an integrated phased test including a four-level diagnostic test.  Integrated phased tests with valid, reliable and practical categories. The results of the measurement of the students' science concept understanding profile on temperature, heat and expansion materials obtained an average understanding of concepts with a low category. The average misconception of students in the material Temperature, Heat and Expansion was obtained at 63% with a high category. The causes of misconceptions in students include their own thoughts, workbook books, and learning resources available on the internet. The integrated gradual test is able to reveal the profile of students' concept understanding and misconceptions so that science learning outcomes are of higher quality.